The Influence of School Culture, Teamwork, and Work Motivation on the Normative Commitment of Public Senior and Vocational High School Teachers in Teluk Batang District - Sahudi Sahudi; Usman Radiana; Eni Rosnija; Urai Salam; Marinu Waruwu (FKIP - Universitas Riau, 2026)
Normative commitment plays an important role in shaping teachers’ loyalty and responsibility to their institutions. Differences in commitment levels are often influenced by school culture, teamwork, and individual work motivation. This study aims to analyze the influence of these three factors on the normative commitment of public senior and vocational high school teachers in Teluk Batang District. The research used a quantitative approach with an associative design. The sample consisted of 65 teachers 24 civil servants and 41 non-civil servants who had taught for at least one year. Because the population was fewer than 100 individuals, total sampling was applied. Data were gathered through questionnaires and analyzed using simple and multiple linear regression with SPSS version 31. The results show that school culture significantly influences normative commitment with a contribution of 52.7%. Teamwork also has a significant effect, contributing 19.7%, while work motivation contributes 28.6%. Simultaneously, the three variables show a combined influence of 85.8% on normative commitment. In conclusion, school culture, teamwork, and work motivation each play a meaningful role in strengthening teachers’ normative commitment. Strengthening these aspects should be prioritized in school management to reinforce teachers’ loyalty and sense of responsibility.